Kattungens behov och rådgivning till dess ägare - Mattsson, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
The cat has become a popular pet. To secure a prosperous cat-human relationship, the cat owner has to understand what kind of animal the cat is and what requirements need to be fulfilled. The purpose of this literature review is to summarize kittens’ needs of socialization, anthelmintics, nutrition, vaccination and gonadectomy, until the age of six months and to give the cat owner information on how to care for the cat during this period. Articles were search for in ScienceDirect, Primo and Scopus. The criteria for the articles to be in this study were that they should be peer-reviewed. The result shows that neonatal kitten is mostly taken care of by the queen however, the owner has to make sure the kitten is healthy and developing correctly. As the kitten grows older it requires more of the surroundings. The socialization period is an important part of the kittens’ life. This period will determine the character of the cat as an adult. It is the breeders’ responsibility to stimulate the kitten during the socialization period that occurs between three to nine weeks of age, when the kitten needs to be handled and exposed to different situations. Environmental enrichment, stimulating all the cats’ senses, is important for both kittens and older cats to avoid behavioral problems. Even small kittens can get infected by endoparasites. There is especially one species of nematodes that infect the young kitten, Toxocara cati. This nematode infects the kitten through the colostrum. To make sure the kitten stays healthy it needs to get anthelmintics, unless the queen doesn’t have outdoor access. Nutrition is an important factor for the growing kitten. It requires energy enough to grow and become a healthy adult. The weaning starts at approximately three to four weeks of age. In the beginning the kitten only eats small amounts of food. Gradually it becomes more and more independent until the kitten is ready to leave the queen at twelve weeks of age. To protect the kitten from infectious diseases it needs to get vaccinated. In Sweden the kittens’ core vaccines protect against Feline herpesvirus (FHV), Feline calicivirus (FCV) and Feline Panleukopenia virus (FPV). The kitten will get three injections at the age of approximately eight weeks, twelve weeks and one year. Vaccination against FHV and FCV should be repeated every year if the cat resides in an area where the virus is common and every third year for FPV. For cats that are not going to be part of a breeding program, a gonadectomy is recommended at the age of six months. A gonadectomy will prevent that unwanted kittens are born as well as lower the risk of the cat developing diseases inflicting the reproductive organ.